ANALYSIS OF TRANSLATION OF THE NON-FINITE FORM OF THE ENGLISH VERB - Izzatulloyeva Maftuna (TADQIQOTLAR, 2025)
Annotation: This article analyzes the translation of non-finite forms of English verbs  into  several  languages,  emphasizing  their  structural  and  functional characteristics.  The  research  examines  the  translation  of  infinitives,  gerunds,  and participles into target languages, assessing the difficulties translators encounter in maintaining semantic, grammatical, and stylistic subtleties. The essay elucidates ways for addressing disparities in language systems and underscores the significance of context  in  attaining  precise  and  natural  translations  through  examples  and comparative study. The results enhance comprehension of verb forms in translation studies and offer pragmatic suggestions for translators.